(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to evaluate the efficacy and safety of Cao Kim Cuong Dong A-D on fasting plasma glucose (FBG), glycated hemoglobin (HbA1c), blood lipid profile, and liver and kidney functions in patients with type 2 diabetes mellitus (T2DM). Methods: This interventional study included 60 patients with T2DM presenting with baseline fasting plasma glucose levels of 7–10 mmol/L and HbA1c < 8%. were enrolled and divided into two groups: Group 1: Thirty newly diagnosed T2DM patients who had been managed with diet and physical activity for at least one month. Group 2: Thirty T2DM patients receiving a single oral hypoglycemic drug for at least one month but have not achieved target glycemic control, including blood glucose and HbA1c levels. All participants received Cao Kim Cuong Dong A-D at a dose of 10 g/day for 90 days. Results: Following 90 days of intervention, significant reductions in fasting plasma glucose and HbA1c levels were observed in both study groups (p < 0.05). The proportion of patients achieving target fasting glucose and HbA1c was 76.7% in Group 1 and 30% in Group 2. No adverse clinical effects were observed during the study period. Conclusion: Cao Kim Cuong Dong A-D demonstrated beneficial effects in reducing fasting blood glucose and HbA1c in patients with type 2 diabetes mellitus with baseline fasting glucose of 7–10 mmol/L and HbA1c < 8%, and was well tolerated after 90 days of use.